Marketing management and productivity the case of internet cafe around UPV (city campus) - Libatique, Clarisse; Paraunda, Rinalyn; Padohinog, Jenalyn; Ramos, Chriszela; Santacera, Jazel (2009)
The study describes the marketing management of the internet cafe's located around UPV (City Campus). It also establishes the relationship between marketing strategies and the productivity of the internet cafe's and determines the level of effectiveness of these strategies. Ten internet cafes were studied and ten respondents were selected through a convenient sampling. The cafes selected came from Iloilo City and are located arond the UPV (city campus) specifically at Ybiernas St., Gen. Luna St. and Infante St. Data and information from the survey questionnaire was coded for proper identification and categorization. These categorized responses were organized and presented in appropriate tables. Responses to probe question that are qualitative in nature translated into categories to facilitate analysis and reporting. Findings of the study presents a favorable response on the relationship of marketing management and the productivity internet cafes. Promotional tools utilized by internet cafes are seen to be "high". Most of the internet cafes responded positively regarding the effects of marketing strategy in their productivity. The percentage of respondents who said yes to the positive effects of marketing strategies are greater than those percentage of those who said no and those who did not responded. Findings reveal the marketing management is positively correlated with internet cafes productivity. The tools in marketing management like price, place, promotions and service contribute to the relation of old customers and attainment of new ones. Over all, marketing management really affects the productivity as well as the profitability of the internet cafes. Realizing the important relationship between the two, the group recommends that the internet cafe should continuously apply the strategies (discounts, posters, lower internet and printing service charge, etc.) and still be open for improvements. Recommendations include the welcoming of comments/feedbacks by placing a suggestion's box, daily scanning of computers for file's protection, expansion of operational area and by encouraging the staff to be more customer friendly and to assist the customers in any way possible. The recommendations aims to help the internet cafes in adding value to their services. Adding values means exceeding customers expectation from your services thus creating greater satisfaction and building a good customer-internet service provider relationship. Building a good relationship will encourage a customer loyalty to the cafe. with a loyal customers the cafe will be able to have a good networking and connection to other potential customers. Therefore, internet cafes will be able to retain customers as well as gain potential ones.
[Research Paper]. -- Iloilo City : UPV-[CM], October 14, 2009.